Texas People's Court : The Fascinating World of the Justice of the Peace - Dunn, Mark, 1956- (Book collections on Project MUSE., 2022)
"From 1983 to 1987, author Mark Dunn worked as a court clerk for a justice of the peace in Travis County, Texas, where, he says, "I learned more about human nature . . . than I could have learned in any other job I might have taken up as a bushy-tailed kid from Tennessee." Based on interviews with 200 justices of the peace from all parts of Texas, Texas People's Court promises to take readers on a tour of what it means to be a Texas justice of the peace: an experience that is by turns hilarious, sobering, heart-wrenching, and, from one end to the other, fascinating. Here in the Texas justice court, wrongs can be righted and lives changed in profound ways. A priceless family necklace might finally be restored to the rightful owner; an occupational driver's license fortuitously granted. A death inquest may become an opportunity for family reflection and valediction, with the attending judge as sympathetic witness. In each of its chapters, Texas People's Court takes up a different aspect, duty, or area of thought related to the profession of justice of the peace taken from conversations with JPs throughout the state of Texas-from those who serve in its most populous municipalities to rural county JPs-putting a human face on the responsibilities, attitudes, and perspectives that motivate their judgments. The result is a thoroughly entertaining, sympathetic view of what Dunn calls "the day-to-day observation of human conflict in microcosm.""--